Wpływ pożaru na populacje drobnych ssaków terenów otwartych – przegląd literatury - Borowski, Zbigniew (Leśne Prace Badawcze, 2024)
Fire is a disturbance that influences global ecosystem structure and function. It is also widely used as a management tool to achieve conservation goals. Wildfires can have highly destructive effects on habitats and their biota. Non-volant animals, such as small mammals, are among the most vulnerable to fire. To date, little is known about the reaction of these animals to fire events in fire-adepted, fast-recovering habitats. Here, we present a systematic literature review to analyse and evaluate the impact of fire on small mammals in open habitats. Most studies were carried out in the New World (Australia, North and South America) in fire-prone habitats. Most of them (74%) focused on forests, and only a quarter (26%) were conducted in habitats with herbaceous vegetation. These 15 articles formed the basis for analysing the response of small mammals living in open areas to fire disturbance. Surprisingly, the effects of fire were of short duration (less than one year) in most studies, and the regeneration of small mammal communities was related to the rate of regeneration of vegetation cover and habitat structure. A crucial factor was fire intensity; the highest diversity of small mammals was associated with low-intensity fires, that resulted in unburned habitat patches (so-called microrefugia). In open areas such as pastures, prairies and meadows, small mammals can survive fires in shelters such as burrows. This systematic review demonstrates that there is a continued focus almost exclusively on fire-prone habitats, whereas due to global change, fire disturbances will be more common and severe in „fire naive” ecosystems in boreal and temperate zones. Significant gaps in the understanding of the recovery ecology of small mammals in open habitats after fires have been identified. Future research should focus on how individual traits of small mammals affect their settling success in burnt habitats.